Metatranscriptomic outlook on green and brown food webs in acid mine drainage. Issue 5 (11th May 2021) - Plewniak, Frédéric; Crognale, Simona; Bruneel, Odile; Sismeiro, Odile; Coppée, Jean‐Yves; Rossetti, Simona; Bertin, Philippe
Abstract : Acid mine drainages (AMDs), metal‐rich acidic effluents generated by mining activities, are colonized by prokaryotic and eukaryotic microorganisms widely distributed among different phyla. We compared metatranscriptomic data from two sampling stations in the Carnoulès AMD and from a third station in the nearby Amous River, focussing on processes involved in primary production and litter decomposition. A synergistic relationship between the green and brown food webs was favoured in the AMD sediments by the low carbon content and the availability of mineral nutrients: primary production of organic matter would benefit C‐limited decomposers whose activity of organic matter mineralization would in turn profit primary producers. This balance could be locally disturbed by heterogeneous factors such as an input of plant debris from the riparian vegetation, strongly boosting the growth of Tremellales which would then outcompete primary producers. In the unpolluted Amous River on the contrary, the competition for limited mineral nutrients was dominated by the green food web, fish and bacterivorous protists having a positive effect on phytoplankton. These results suggest that in addition to direct effects of low pH and metal contamination, trophic conditions like carbon or mineral nutrient limitations also have a strong impact on assembly and activities of AMDs' microbial communities.